Cassava stems: a new resource to increase food and fuel production. Issue 1 (9th September 2013) - Zhu, Wanbin; Lestander, Torbjörn A.; Örberg, Håkan; Wei, Maogui; Hedman, Björn; Ren, Jiwei; Xie, Guanghui; Xiong, Shaojun
Abstract Given the growing global population, mankind must find new ways to lower competition for land between food and fuel production. Our findings for cassava suggest that this important crop can substantially increase the combined production of both food and fuel. Cassava stems have previously been overlooked in starch and energy production. These food‐crop residues contain about 30% starch (dry mass) mostly in the xylem rather than phloem tissue. Up to 15% starch of the stem dry mass can be extracted using simple water‐based techniques, potentially leading to an 87% increase in global cassava starch production. The integration of biofuel production, using residues and wastewater from starch extraction, may bring added value. The cassava roots on which biofuels and other products are based can be replaced by cassava stems without land use expansion, making root starch available as food for additional 30 million people today.